RTS,S vaccination is associated with reduced parasitemia and anemia among children diagnosed with malaria in the outpatient department of a district hospital in rural Malawi - Todd, Jacob L.; Topazian, Hillary M.; Zulu, Madalitso; Mafunga, Pilirani; Mapanje, Clement; Kaphatika, James G.; Chagomerana, Maganizo B.; Hoffman, Irving; Juliano, Jonathan J.; Mvalo, Tisungane (Frontiers in Epidemiology, 2022)
The RTS,S/AS01 malaria vaccine was recently approved by the World Health Organization, but real-world effectiveness is still being evaluated. We measured hemoglobin concentration and parasite density in vaccinated and unvaccinated children who had been diagnosed with malaria by rapid diagnostic test (mRDT) in the outpatient department of a rural hospital in Malawi. Considering all mRDT positive participants, the mean hemoglobin concentration among unvaccinated participants was 9.58 g/dL. There was improvement to 9.82 g/dL and 10.36 g/dL in the 1 or 2 dose group (p = 0.6) and the 3 or 4 dose group (p = 0.0007), respectively. Among a microscopy positive subset of participants, mean hemoglobin concentration of unvaccinated participants was 9.55 g/dL with improvement to 9.82 g/dL in the 1 or 2 dose group (p = 0.6) and 10.41 g/dL in the 3 or 4 dose group (p = 0.003). Mean parasite density also decreased from 115,154 parasites/μL in unvaccinated children to 87,754 parasites/μL in children who had received at least one dose of RTS,S (p = 0.04). In this study population, vaccination was associated with significant improvements in both hemoglobin concentration and parasite density in the setting of real-world administration of the RTS,S/AS01 vaccine.